Kertas Indikator Asam Basa dari Ekstrak Etanol Bunga Asoka (Ixora coccinea Linn) dengan Variasi Pelarut dan Lama Perendaman - Riyanti Riyanti; Putut Marwoto; Sigit Priatmoko; Edy Cahyono (Postgraduate, University of Mataram, 2022)
This research developed a paper indicator made from extracted Ashoka flower, Ixora coccinea Linn, with solvent and the soaking period variances. Ashoka flower is a plant containing anthocyanin pigment. The plant is sensitive to acidic levels of pH. The content of the Ashoka flower brings significant potential as a natural indicator. The researchers extracted the anthocyanin pigment of the lower with the maceration method with 96% and 70% ethanol solvents for 24 hours. The researchers calibrated the extracted ethanol with buffer solution under pH 1-12. Then, the researchers cut 42 Whatman papers sized Â±5x1 cm. The researchers put the papers into the mixtures of the extracted ethanol within 48 - 72 hours of the soaking period. After that, the researchers dried out the papers and examined the solution in terms of acid-base level. The papers made of extracted ethanol from Ashoka flower on solutions of HCl, CH3COOH, NH4OH, NaOH had their colors changed into brighter pink, pink, light green, and green-brownish. The color changes on the developed paper indicators made of extracted ethanol from Ashoka were extremely clear with a condition of 96% ethanol solution and 72 hours of soaking period.